2020
DOI: 10.1038/s41598-020-72261-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq identifies unique transcriptional landscapes of human nucleus pulposus and annulus fibrosus cells

Abstract: Intervertebral disc (IVD) disease (IDD) is a complex, multifactorial disease. While various aspects of IDD progression have been reported, the underlying molecular pathways and transcriptional networks that govern the maintenance of healthy nucleus pulposus (NP) and annulus fibrosus (AF) have not been fully elucidated. We defined the transcriptome map of healthy human IVD by performing single-cell RNA-sequencing (scRNA-seq) in primary AF and NP cells isolated from non-degenerated lumbar disc. Our systematic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 78 publications
2
63
0
Order By: Relevance
“…2e), and highly expressed IBSP and CYTL1, which are NP-negative biomarkers (Supplementary Table 3). 17,52 Moreover, subclusters C1 and C2 showed a higher percentage of cells arrested in the G2/ M phase than that in others, which was indicative of relatively higher proliferative activity (Fig. 2f).…”
Section: Resultsmentioning
confidence: 90%
“…2e), and highly expressed IBSP and CYTL1, which are NP-negative biomarkers (Supplementary Table 3). 17,52 Moreover, subclusters C1 and C2 showed a higher percentage of cells arrested in the G2/ M phase than that in others, which was indicative of relatively higher proliferative activity (Fig. 2f).…”
Section: Resultsmentioning
confidence: 90%
“…Taken together, our data indicate a series of very distinct cell populations that are closely orchestrated living in this unique environment. Our data, whether in the single-cell RNAseq or the bulk RNAseq, show that we could identify most NP specific markers and genes previously reported to be expressed at higher levels in the NP than in the AF [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 87%
“…Beyond development, planarian scRNA-seq revealed that muscles produce most of the matrisome, and inhibiting one key matrisome gene (hemicentin) resulted in severe epidermal ruffling and displacement of cells during homeostatic tissue turnover, suggesting an important role for tissue regeneration [28] . Furthermore, in healthy human lumbar discs, the core matrisome can be used to distinguish primary annulus fibrosus and nucleus pulposus cells based on 90 out of the 274 core matrisome genes being differentially expressed in the opposite direction using scRNA-seq [35] . Similarly, 115 matrisome genes are characteristically expressed in the six cell types that make up the human cutaneous neurofibroma microenvironment [36] .…”
Section: Discussionmentioning
confidence: 99%